Pengangguran Terdidik : Analisis Faktor Yang Mempengaruhi dan Upaya Penanggulangannya. - Erni Febrina Harahap; Akmal Yusuf (Jurnal Ekonomi Sakti, 2025)
ABSTRACT This study analyse the influence of education level, average wages, employment opportunities, and economic growth on educated unemployment in West Sumatra from 2017 to 2023. The quantitative method used panel data combining time series and cross-sectional data of 19 districts/cities, analysed using a Fixed Effect regression model. Results indicate that all independent variables significantly affect educated unemployment jointly, with an R-squared of 96.82%. Partially, education level and employment opportunities have significant positive effects, while economic growth has a significant negative effect. Average wages have a positive but not significant effect. These findings indicate a mismatch between educational attainment and labor market needs in the region. The need for enhanced graduate skill development and policies that steer economic growth toward creating jobs suitable for educated workers. This study provides a basis for regional government policy recommendations to reduce educated unemployment and improve labor absorption in West Sumatra.